Evaluating the Inclusion of Vocal Training in Spain’s Teacher Education: A Quantitative Analysis - Saray Prados-Bravo; Diego González-Rodríguez; Agustín Rodríguez-Esteban (Education Sciences)
The curricula of bachelor’s and master’s degrees in education should provide optimal tools for teaching practice. An analysis of these curricula in Spanish universities reveals a lack of vocal training. The aim of the present study is to determine whether vocal training in these courses leads to greater knowledge of vocal patterns and techniques, which could lead to greater satisfaction and a lower tendency to abandon the profession. A descriptive–comparative and predictive quantitative study was carried out using an ex post facto, non-experimental, cross-sectional design. The sample consisted of 519 pre-school, primary, and secondary school teachers from all over Spain. The results have confirmed that there is a correlation between having received initial training in vocal hygiene and singing and a tendency to take additional courses in these areas. Furthermore, there is evidence that women and teachers with vocal disorders of the type studied are more aware of voice care in their profession. Finally, a lack of correlation was observed between the training received and the degree of knowledge about vocal health and hygiene. This suggests that both the quantity and quality of training in this area should be increased.